Assessment of seed quality parameters and effect of physical and chemical treatments on seed germination of Myriophyllum Spicatum L. - Wani, Aijaz Ahmad; Arshid, Shahzada (Comunicata Scientiae, 2013)
The present study was undertaken to understand the fruit and seed morphology, seed viability and effect of various physical and chemical factors on seed germination allowing us to explore the spread potential and/or seedling recruitment mechanism in Myriophyllum spicatum L.. The fruit of the species is a schizocarp, while as seed is a nutlet. The seed set was recorded to be ranging from 70.98-77.91% across the standing water populations, whereas no seed set was observed in running water populations due to the lack of an effective pollination system. The seed viability ranged from 85-90%. For in-vitro seed germination studies, the seeds were subjected to different physical and chemical treatments under alternate light and dark as well as continuous dark conditions. The seeds in control and those treated with different concentrations of GA3 and IAA and those whose epicarp and mesocarp were removed did not show any signs of germination. However, it was observed that surgical exposure of the embryo (cutting of hard endocarp of seed) has a promoter effect on germination and maximum percentage germination (76.66 ± 5.77) was recorded due to surgical exposure of embryo plus different concentrations of GA3. Moreover, a good germination percentage was recorded in seeds subjected to chilling treatment. Further, it was observed that seed germination of one-year-old seeds was less if compared to the current year seeds and overall percentage germination was higher in alternate light and dark if compared to continuous dark conditions in all the treatments.Thus, we conclude that the dormancy of the seeds is due to the hard endocarp and that the light has a promoting effect on germination. With the increase in the age of the seeds, there is decrease in their viability and hence germination. The chilling winter temperature of the Kashmir is responsible for breaking the hard endocarp of the seeds leading to their germination and hence spread of the populations.